Direct detection of odd-frequency superconductivity via time- and angle-resolved photoelectron fluctuation spectroscopy - Viktoriia Kornich; Frank Schlawin; Michael A. Sentef; Björn Trauzettel (Physical Review Research, 2021)
We propose a measurement scheme to directly detect odd-frequency superconductivity via time- and angle-resolved photoelectron fluctuation spectroscopy. The scheme includes two consecutive nonoverlapping probe pulses applied to a superconducting sample. The photoemitted electrons are collected in a momentum-resolved fashion. Correlations between signals with opposite momenta are analyzed. Remarkably, these correlations are directly proportional to the absolute square of the time-ordered anomalous Green's function of the superconductor. This setup allows for the direct detection of the “hidden order parameter” of odd-frequency pairing. We illustrate this general scheme by analyzing the signal for the prototypical case of a two-band superconductor.